2019
DOI: 10.1111/aor.13557
|View full text |Cite
|
Sign up to set email alerts
|

Generation of microbubbles in extracorporeal life support and assessment of new elimination strategies

Abstract: Occurrence of microbubbles (MB) is a major problem during venoarterial extracorporeal life support (ECLS) with partially severe clinical complications. The aim of this study was to establish an in vitro ECLS setup for the generation and detection of MB. Furthermore, we assessed different MB elimination strategies. Patient and ECLS circuit were simulated using reservoirs, a centrifugal pump, a membrane oxygenator, and an occluder (modified roller pump). The system was primed with a glycerin solution of 44%. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Currently, the standard circuit consists of a membrane oxygenator and a centrifugal pump, through which the non-physiological flow leads to microcirculatory malperfusion. 5,6 Recently, several pumps allowing for pulsatile flow have been developed. 3,7,8 The novel i-Cor system (Xenios AG, Heilbronn, Germany) consists of a diagonal blood pump that provides pulsatility triggered by electrocardiogram and has been applied in Europe for several years.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the standard circuit consists of a membrane oxygenator and a centrifugal pump, through which the non-physiological flow leads to microcirculatory malperfusion. 5,6 Recently, several pumps allowing for pulsatile flow have been developed. 3,7,8 The novel i-Cor system (Xenios AG, Heilbronn, Germany) consists of a diagonal blood pump that provides pulsatility triggered by electrocardiogram and has been applied in Europe for several years.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the rotational speed of ECMO is another concern. Literature review and our own air embolism experiments have shown that low rotational speed can reduce the formation of microbubbles in the return blood[ 8 , 9 ]. In the present case, the initial rotational speed was 2000 rpm, along with the close monitoring of flow volume and bubbles in the circuit.…”
Section: Discussionmentioning
confidence: 99%
“…МП, несмотря на малые размеры, имеют дифференциацию. Некоторые исследователи разделяют пузырьки на: <50 мкм -очень маленькие, к которым относят МП; 50-100 мкм -маленькие; 100-150 мкм -средние; 150-300 мкм -большие; >300 мкм -очень большие [11]. Другие относят к МП все объекты, которые могут измерить текущие системы регистрации в контуре аппаратов ВК (от 5-10 до 250-500 мкм) [12].…”
Section: Introductionunclassified